Host serum iron modulates dengue virus acquisition by mosquitoes - Zhu, Yibin; Tong, Liangqin; Nie, Kaixiao; Wiwatanaratanabutr, Itsanun; Sun, Peng; Li, Qingqing; Yu, Xi; Wu, Pa; Wu, Tianshi; Yu, Chen; Liu, Qiyong; Bian, Zhongqi; et al. (My University, 2019)
A blood meal is the primary route through which mosquitoes acquire an arbovirus infection. Blood components or their metabolites may regulate the susceptibility of mosquitoes to arboviruses. Here we report that serum iron in human blood influences dengue virus acquisition by mosquitoes. Dengue virus acquisition by Aedes aegypti was inversely correlated with the iron concentration in serum from human donors. In a mouse–mosquito acquisition model, iron supplementation reduced dengue virus prevalence and viral load, whereas neutralization of serum iron facilitated dengue virus infection in A. aegypti mosquitoes. Of note, mosquitoes feeding on iron-deficient (sideropenic) mice exhibited a higher prevalence of dengue virus. Reversal of the sideropenic status of hosts largely reduced dengue virus acquisition and infection by mosquitoes. Serum iron, rather than haem-bound iron, was utilized by the mosquito iron metabolism pathway to boost the activity of reactive oxygen species in the gut epithelium, subsequently inhibiting infection by dengue virus. On the basis of these results, a status of iron deficiency in the human population might contribute to the vectorial permissiveness to dengue virus, thereby facilitating its spread by mosquitoes.